The Dogma of Dingoes—Taxonomic status of the dingo: A reply to Smith et al. - Jackson, Stephen M.; Fleming, Peter J.s.; Eldridge, Mark D.b.; Ingleby, Sandy; Flannery, Tim; Johnson, Rebecca N.; Cooper, Steven J.b.; Mitchell, Kieren J.; Souilmi, Yassine; Cooper, Alan; Wilson, Don E.; Helgen, Kristofer M. (Zootaxa, 2019)
Adopting the name Canis dingo for the Dingo to explicitly denote a species-level taxon separate from other canids was suggested by Crowther et al.  (2014) as a means to eliminate taxonomic instability and contention. However, Jackson et al.  (2017), using standard taxonomic and nomenclatural approaches and principles, called instead for continued use of the nomen C. familiaris for all domestic dogs and their derivatives, including the Dingo. (This name, C. familiaris, is applied to all dogs that derive from the domesticated version of the Gray Wolf, Canis lupus, based on nomenclatural convention.) The primary reasons for this call by Jackson et al.  (2017) were: (1) a lack of evidence to show that recognizing multiple species amongst the dog, including the Dingo and New Guinea Singing Dog, was necessary taxonomically, and (2) the principle of nomenclatural priority (the name familiaris Linnaeus, 1758, antedates dingo Meyer, 1793). Overwhelming current evidence from archaeology and genomics indicates that the Dingo is of recent origin in Australia and shares immediate ancestry with other domestic dogs as evidenced by patterns of genetic and morphological variation. Accordingly, for Smith et al.  (2019) to recognise Canis dingo as a distinct species, the onus was on them to overturn current interpretations of available archaeological, genomic, and morphological datasets and instead show that Dingoes have a deeply divergent evolutionary history that distinguishes them from other named forms of Canis (including C. lupus and its domesticated version, C. familiaris). A recent paper by Koepfli et al.  (2015) demonstrates exactly how this can be done in a compelling way within the genus Canis—by demonstrating deep evolutionary divergence between taxa, on the order of hundreds of thousands of years, using data from multiple genetic systems. Smith et al.  (2019) have not done this; instead they have misrepresented the content and conclusions of Jackson et al.  (2017), and contributed extraneous arguments that are not relevant to taxonomic decisions. Here we dissect Smith et al.  (2019), identifying misrepresentations, to show that ecological, behavioural and morphological evidence is insufficient to recognise Dingoes as a separate species from other domestic dogs. We reiterate: the correct binomial name for the taxon derived from Gray Wolves (C. lupus) by passive and active domestication, including Dingoes and other domestic dogs, is Canis familiaris. We are strongly sympathetic to arguments about the historical, ecological, cultural, or other significance of the Dingo, but these are issues that will have to be considered outside of the more narrow scope of taxonomy and nomenclature.